A unique method to produce transgenic embryos in ovine, porcine, feline, bovine and equine species - Pereyra Bonnet, Federico Alberto (2008)
Transgenesis is an essential tool in many biotechnological applications. Intracytoplasmic sperm injection (ICSI)-mediated gene transfer is a powerful technique to obtain transgenic pups; however, most domestic animal embryos do not develop properly after ICSI. An additional step in the protocol, namely assistance by haploid chemical activation, permits the use of ICSI-mediated gene transfer to generate transgenic preimplantation embryos in a wide range of domestic species, including ovine, porcine, feline, equine and bovine. In the present study, spermatozoa from five species were coincubated with pCX-EGFP plasmid and injected into metaphase II oocytes. The chemical activation protocol consisted of ionomycin plus 6-dimethylaminopurine. We detected high proportions of fluorescent EGFP embryos for all five species (23-60%), but with a high frequency of mosaic expression (range 60-85%). To our knowledge, this is the first study to produce exogenous DNA expression in feline and equine embryos. Chemical activation reduces the lag phase of egfp expression in ovine embryos. Our results show that this unique method could be used to obtain ovine, porcine, feline, bovine and equine transgenic preimplantation embryos. © CSIRO 2008.